2022
DOI: 10.33073/pjm-2022-020
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota, a Potential Determinant for the Treatment Efficacy of Gastric Helicobacter pylori Eradication in Humans

Abstract: The oral cavity serves as another reservoir for gastric Helicobacter pylori and may contribute to the failure of gastric H. pylori eradication therapy. However, changes to the oral microbial composition after gastric H. pylori eradication therapy has not yet been identified. This study aims to dissect whether the oral microbiota is involved and which bacterium mediates the clinic failure in H. pylori eradication. In the present study, the oral microorganisms from patients who had received the gastric H. pylori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, currently, applied eradication regimens have low apparent efficacy against oral H. pylori . Studies have shown that H. pylori can still be detected in the oral cavities of patients who have undergone successful gastric eradication [ 12 , 16 ]. Furthermore, the current H. pylori eradication regimens involve long-term antibiotic administration that causes side effects severe enough to reduce patient compliance and adherence.…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, applied eradication regimens have low apparent efficacy against oral H. pylori . Studies have shown that H. pylori can still be detected in the oral cavities of patients who have undergone successful gastric eradication [ 12 , 16 ]. Furthermore, the current H. pylori eradication regimens involve long-term antibiotic administration that causes side effects severe enough to reduce patient compliance and adherence.…”
Section: Introductionmentioning
confidence: 99%